2014
DOI: 10.1016/j.msec.2014.03.065
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable electrospun nanofibers coated with platelet-rich plasma for cell adhesion and proliferation

Abstract: Biodegradable electrospun poly(ε-caprolactone) (PCL) scaffolds were coated with platelet-rich plasma (PRP) to improve cell adhesion and proliferation. PRP was obtained from human buffy coat, and tested on human adipose-derived mesenchymal stem cells (MSC) to confirm cell proliferation and cytocompatibility. Then, PRP was adsorbed on the PCL scaffolds via lyophilization, which resulted in uniform sponge-like coating of 2.85 (s.d. 0.14) mg/mg. The scaffolds were evaluated regarding mechanical properties (Young’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
61
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 44 publications
8
61
0
Order By: Relevance
“…The results are similar to those of Diaz-Gomez et al, 15 who observed that adhesion of PRP to PCL nanofibers promotes proliferation of MSCs. Similarly, Buzgo et al 58 found that embedded alpha granules were able to stimulate the chondrogenic differentiation of MSCs.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…The results are similar to those of Diaz-Gomez et al, 15 who observed that adhesion of PRP to PCL nanofibers promotes proliferation of MSCs. Similarly, Buzgo et al 58 found that embedded alpha granules were able to stimulate the chondrogenic differentiation of MSCs.…”
supporting
confidence: 91%
“…The study showed that the platelets improved the properties of PCL nanofibers. In a study by Diaz-Gomez et al, 15 PCL nanofibers prepared using electrospinning were soaked in platelet-rich plasma (PRP) and subsequently lyophilized. It was shown that growth factors were released from the scaffold-enhanced adhesion and proliferation of mesenchymal stem cells (MSCs).…”
Section: Introductionmentioning
confidence: 99%
“…In alveolar bone cells higher concentrations of PRP suppressed proliferation whereas low concentrations (1-5%) stimulated proliferation [31]. Regardless, PRP exerts a stimulatory effect on the proliferation of stem cells such as MSCs (Figure 2A), exhibiting also dose dependency [41-46]. Murphy and colleagues have shown that PRP derived from human umbilical cord blood had higher proliferation rates in MSCs compared to normal blood [43].…”
Section: Effects Of Platelet Rich Plasma In Tissue Engineeringmentioning
confidence: 99%
“…Although the stimulation of (stem) cell proliferation could be a multifactorial event due to the numerous distinct proliferation stimulating molecules, Stat3/p27 Kip1 promotion of cell cycle progression has been identified as a mechanism [39]. Moreover, PRP can also indirectly stimulate proliferation by enhancing (stem) cell adhesion, highlighting the use of PRP for increased (stem) cell adherence in biomaterials [46]. Besides proliferation, PRP can contribute to an increase in cell expansion rates by reducing cell death.…”
Section: Effects Of Platelet Rich Plasma In Tissue Engineeringmentioning
confidence: 99%
“…Accordingly, random nanofibers have been recently reported to significantly improve rat MSC proliferation compared to aligned nanofibers [99]. The [96] or in combination with sonic Hedgehog [105], graphene oxide [106], bioceramics [107], growth factors [108], acellular pericardium [109], platelet-rich plasma [110], collagen [104], fibronectin [111], and mussel inspired DOPA-melanin coating for the adsorption of siRNA targeting RE-1 silencing transcription factor [112]. In all cases, depending on the desired application, nanostructural surfaces (whether scaffolds or membranes) have been reported to provide a suitable system to support adhesion and growth of the cell type of interest, and to influence progenitor population activity and function, holding promise for tissue regeneration applications.…”
Section: Accepted Manuscriptmentioning
confidence: 99%